2023
DOI: 10.3390/diagnostics13030373
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Sequencing (NGS) and Third-Generation Sequencing (TGS) for the Diagnosis of Thalassemia

Abstract: Thalassemia is one of the most heterogeneous diseases, with more than a thousand mutation types recorded worldwide. Molecular diagnosis of thalassemia by conventional PCR-based DNA analysis is time- and resource-consuming owing to the phenotype variability, disease complexity, and molecular diagnostic test limitations. Moreover, genetic counseling must be backed-up by an extensive diagnosis of the thalassemia-causing phenotype and the possible genetic modifiers. Data coming from advanced molecular techniques s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 135 publications
1
9
0
Order By: Relevance
“…According to the present study different abnormalities were found in the evaluated patients and it was observed that eye abnormalities were found with high frequency of 35% followed by skin abnormality 17%, bone and joint abnormality13 %, ear abnormality 8% and mental abnormality 02 % while 25 % of evaluated member of the population were normal with no visible physical abnormality. The present study has some similarities with the study performed by Erickson et al, (1980) 27 . According to their study 15% of patients were having Superficial skin infections (tinea versicolor, other scabies, mycosis and pediculosis), 10% with psychiatric problems, 8% were having Otorhinological problems (deafness, otitis media, chronic sinusitis), and 6% were having opthalmological problems (conjunctivitis, cataract) 28 .…”
Section: Discussionsupporting
confidence: 91%
“…According to the present study different abnormalities were found in the evaluated patients and it was observed that eye abnormalities were found with high frequency of 35% followed by skin abnormality 17%, bone and joint abnormality13 %, ear abnormality 8% and mental abnormality 02 % while 25 % of evaluated member of the population were normal with no visible physical abnormality. The present study has some similarities with the study performed by Erickson et al, (1980) 27 . According to their study 15% of patients were having Superficial skin infections (tinea versicolor, other scabies, mycosis and pediculosis), 10% with psychiatric problems, 8% were having Otorhinological problems (deafness, otitis media, chronic sinusitis), and 6% were having opthalmological problems (conjunctivitis, cataract) 28 .…”
Section: Discussionsupporting
confidence: 91%
“…Compared with the second-generation sequencing technology, TGS technology overcomes some NGS shortcomings in genome assembly. TGS does not require polymerase chain reaction (PCR) amplification or long read length and has no guanine-cytosine (GC) preference, thus making genome assembly using PacBio Hi-Fi an effective assembly strategy [ 29 , 30 ]. Compared with the previously published 841 Mb (N50 = 122 kb) genome assembly of white clover, the genome size in this study was 1,095 Mb (contig N50 = 14 Mbp), indicating a significantly improved quality.…”
Section: Discussionmentioning
confidence: 99%
“…Large deletions are typically found by gap-PCR or MLPA, while point mutations and indels are typically detected by MARMS-PCR or sequencing. A homozygous Ī²-thalassemia detected using MARMS-PCR and sequencing may not be a true homozygote but rather a compound heterozygote with a deletional Ī²-thalassemia or a Ī“Ī²-thalassemia that must be ruled out using gap-PCR, MLPA, or cascade screening [ 26 ]. Therefore, a few countries have recently introduced screening for thalassemia or hemoglobinopathies using next-generation sequencing (NGS).…”
Section: Discussionmentioning
confidence: 99%